2007
DOI: 10.1093/humrep/dem244
|View full text |Cite
|
Sign up to set email alerts
|

Cervical priming with sublingual misoprostol prior to insertion of an intrauterine device in nulliparous women: a randomized controlled trial

Abstract: Misoprostol facilitates insertion of an IUD, and reduces the number of difficult and failed attempts of insertions in women with a narrow cervical canal. The optimal regimen of misoprostol remains to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(56 citation statements)
references
References 28 publications
4
46
1
1
Order By: Relevance
“…These pain levels with IUD insertion are consistent with results from recent European and U.S. studies of other pain control interventions. A Swedish study evaluating misoprostol for IUD insertion among nulliparous women reported pain scores of 65-70 mm on a 100-mm VAS [18]. A Dutch study evaluating misoprostol with IUD insertion reported mean pain scores of 54-59 mm in nulliparous and 26-33 mm in multiparous women [19].…”
Section: Discussionmentioning
confidence: 99%
“…These pain levels with IUD insertion are consistent with results from recent European and U.S. studies of other pain control interventions. A Swedish study evaluating misoprostol for IUD insertion among nulliparous women reported pain scores of 65-70 mm on a 100-mm VAS [18]. A Dutch study evaluating misoprostol with IUD insertion reported mean pain scores of 54-59 mm in nulliparous and 26-33 mm in multiparous women [19].…”
Section: Discussionmentioning
confidence: 99%
“…The US Food and Drug Administration in 2005 no longer recommended the copper T380A IUD only for multiparous women. Another reason may be providers' concern about insertion difficulties and pain experienced by nulliparous women during the insertion procedure (8,(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…IUDs provide highly effective (>99%) and cost-effective birth control without the need for daily medication or cooperation of sexual partners, although IUD insertion can be costly and does require a healthcare professional (15). Pain upon IUD insertion may be a significant barrier to women's preparedness to choose this method of contraception (16). Relief from the pain could increase the number of women who would consider having an IUD inserted, with the possible consequence of reducing unwanted pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Young women and those who have not given birth are likely to experience more pain during IUD insertion, as a result of having a relatively narrow cervix (16). These women may be considered to have a greater need for pain relief during IUD insertion than women who have previously given birth, and they are likely to benefit more from the effects of lidocaine.…”
Section: Discussionmentioning
confidence: 99%